The effects of low calorie, high protein diet on body composition, duration and sleep quality on obese adults: A randomized clinical trial - Fatemeh Sadat Hashemi Javaheri; A. R. Ostadrahimi; Mohsen Nematy; Seyyed Mostafa Arabi; Mahnaz Amini (Health Science Reports, 2023)
Abstract Background and Aims The effects of high‐protein diets on regulating sleep have received research attention in recent decades. However, no studies have examined the effects of these diets in obese adults. Therefore, this study was conducted to investigate the effects of low‐calorie high protein diets on sleep quality in obese adults. Methods This study is a randomized clinical trial conducted on 60 obese adults (BMI > 29.9 kg/m2) diagnosed with low‐quality sleep. All participants were given a diet with a 750‐calorie energy deficit. While the control group was given a normal diet, the intervention group received a diet with 30% more protein. Results The results showed a significant difference between the control group and intervention group with respect to sleep apnea at 30‐, 60‐, and 90‐day follow‐up (p < 0.01). Sleep quality, apnea‐hypopnea index (AHI), sleep latency (SL), and polysomnography were significantly different between the two groups (p < 0.05), showing an improvement in sleep quality and obstructive sleep apnea in the intervention group (p < 0.05). Conclusion This study shows that low‐calorie high‐protein diets can effectively improve apnea, sleep quality, and body composition indices in obese adults.